An agent-based model to support the preliminary design and operation of heating and power grids with cogeneration units and photovoltaic panels in densely populated areas. (15th December 2022) - Volpe, R.; Catrini, P.; Piacentino, A.; Fichera, A.
Abstract: The increase in the energy demands of residential neighborhoods constitutes a huge challenge to be faced. A viable option lies in the insertion of both renewable energy production systems and cogeneration units within urban territories. On-site production allows for the satisfaction of the heating and electrical demands of end-users and favors the distribution of produced energy within the neighborhood, especially under the regulatory framework of energy communities. This paper proposes a tool to model heating and electricity networks integrated with cogeneration units and PV panels installed in urban areas. The tool accounts for the following possibilities: (i) energy flow management and power sizes of both heating and electric networks, and (ii) evaluation of the electricity sharing configurations arising within energy communities. To better clarify the capability of the tool in supporting energy analysts and decision-makers, a densely populated area in Southern Italy is proposed as a case study. Regarding thermal distribution, results demonstrated that it is better to plan pipelines extended up to 300 m to take full advantage of the insertion of the CHP in the areas. Different considerations apply to the electrical distribution; here, an energy community extended over a geographical area with a radius of around 100 m is sufficient to guarantee an almost fully connected grid and obtain in any case exceeding production to be released to the centralized network. Highlights: An agent-based model is proposed as a tool for the design and operation of energy networks. Photovoltaic panels and cogeneration units are assumed as the main energy systems. Hourly-based simulations are performed for grid operation in residential and commercial areas. Photovoltaic panels and cogeneration units are suitable technologies favoring autonomy and sharing in energy communities. Results prove the flexibility of the tool in selecting the distribution distance.